Nanocristais de TiO2 : relação entre parâmetros morfológicos, estruturais e fotocatálise - Mendonça, Vagner Romito de (2010)
In this work, morphologically different TiO2 nanocrystals were synthesized through the OPM method with the objective of performing a comparative study related to photoactivity. Morphological characterization was performed with the use of SEM/FEG, DRX and low temperature N2 adsorption. Rhodamine B dye photocatalytic degradation experiments carried out under UVC radiation showed that synthesis at pH around 8 generates a material with higher photoactivity compared to the other values. Measurements of Zeta potential, X-ray absorption at XANES region, Photoluminescence Spectroscopy and HRTEM images were obtained to verify the reason why the materials had different photoactivities. Under the conditions employed, there were two main particle characteristics from synthesis environment interfering in the materials photoactivities: the surface hydroxylation, which has a positive effect on photocatalysis, and the crystalline defects from crystal growth, that has a negative effect. Both characteristics increase with an increase in synthesis pH. The mechanism of degradation by hydroxyl radical attack, generated on the surface of the material, was used to explain the different photoactivities and the optimum synthesis pH. At pH around 8 the material has enough hydroxyl groups in its surface to result in higher photoactivity than those synthesized at lower pH values. And the charge recombination effects generated by defects due to particles oriented growth, which begins in a synthesis environment with pH close to 10, is not acting yet. These two factors cause synthesis at pH around 8 to result in materials with higher photoactivity.